2023
DOI: 10.1002/smll.202207220
|View full text |Cite
|
Sign up to set email alerts
|

Morphology‐Dependent Charge Carrier Dynamics and Ion Migration Behavior of CsPbBr3 Halide Perovskite Quantum Dot Films

Abstract: Exceptional electronic, optoelectronic, and sensing properties of inorganic Cs‐based perovskites are significantly influenced by the defect chemistry of the material. Although organic halide perovskites that have a polycrystalline structure are heavily studied, understanding of the defect properties at the grain boundaries (GB) of inorganic Cs‐based perovskite quantum dots (QDs) is still limited. Here, morphology‐dependent charge carrier dynamics of CsPbBr3 quantum dots at the nanoscale by performing scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Based on these findings, we propose two pathways for the migration of V I s, namely, the grain boundary pathway and the grain interior pathway, to explain the ternary states observed in our RS devices, as summarized in Scheme . Initially, thermal annealing of the PQDs allows surface ligands to detach, which generates iodine vacancies that are preferentially located at GBs to form a few CFs, giving rise to iLRS (Scheme a). During the RESET process, the large current flowing through CF generates significant Joule heat, facilitating the lateral diffusion of iodine vacancies and CF annihilation, transitioning the device from iLRS to HRS (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, we propose two pathways for the migration of V I s, namely, the grain boundary pathway and the grain interior pathway, to explain the ternary states observed in our RS devices, as summarized in Scheme . Initially, thermal annealing of the PQDs allows surface ligands to detach, which generates iodine vacancies that are preferentially located at GBs to form a few CFs, giving rise to iLRS (Scheme a). During the RESET process, the large current flowing through CF generates significant Joule heat, facilitating the lateral diffusion of iodine vacancies and CF annihilation, transitioning the device from iLRS to HRS (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…It may be stated that, as obtained from XPS studies, the electronic arrangement of Pb 2+ is 5d 10 6s 2 6p 0 ; the (6s) 2 lone pair electron configuration of lead remains the driving force in distorting the octahedron. , Both the butterfly and hysteresis loops in the PFM studies could be seen to be shifted to the positive side of the applied voltage (Figure d,e). The imprint phenomena likely originate due to (i) the asymmetry in the trapped charge distribution and/or (ii) the alignment of defect dipoles near the electrode–sample interface. , …”
Section: Resultsmentioning
confidence: 99%
“…Extensive research has been dedicated to improving the efficiency and stability of PSCs by mitigating hysteresis. Previous studies have revealed that GBs in perovskite films play a crucial role in ion migration pathways. , In order to investigate the influence of A-site doping on the GB regions, we utilized KPFM and C-AFM to measure the surface potential and current of the three thin films. The surface potential images of the three thin films under dark and illuminated conditions are depicted in Figure a–f.…”
Section: Results and Discussionmentioning
confidence: 99%